1993
DOI: 10.1051/animres:19930109
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the activity of a fructo-oligo-saccharide on different caecal parameters in rabbits experimentally infected with E coli 0.103

Abstract: Summary — Thirty 51-d-oId rabbits, fed since the l8th d on a mixed diet containing a fructo-oligosaccharide (FOS) added at 0.25% (FOS group) and 30 51-d-old rabbits without FOS (C group) were infected via oesophagal route, with 2 x 10 7 E coli 0.103 strain B lo . Seven (P < 0,001); une augmentation de la densité des colibacilles non pathogènes 1()4, 2 /g versus 10 2 , 5 1g (P < 0,001). Ces résultats confirment l'aptitude du fructo-oligo-saccharide étudié à augmenter la production des AGV au niveau du c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 0 publications
4
22
0
Order By: Relevance
“…Our results are in agreement with the described importance of inulin-type fructans in rabbit nutrition regarding caecal fermentative activity (Morisse et al, 1993;Maertens et al, 2004;Volek et al, 2005;Castellini et al, 2007;Volek et al, 2007;Juśkiewicz et al, 2008). In the present study, dietary supplementation with dried chicory root affected the total caecal concentrations of VFA and the pH when compared with the control diet; these differences were apparently associated with a non-significant lower incidence of diarrhoea in rabbits fed the Chicory 10 diet (Gidenne and Licois, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in agreement with the described importance of inulin-type fructans in rabbit nutrition regarding caecal fermentative activity (Morisse et al, 1993;Maertens et al, 2004;Volek et al, 2005;Castellini et al, 2007;Volek et al, 2007;Juśkiewicz et al, 2008). In the present study, dietary supplementation with dried chicory root affected the total caecal concentrations of VFA and the pH when compared with the control diet; these differences were apparently associated with a non-significant lower incidence of diarrhoea in rabbits fed the Chicory 10 diet (Gidenne and Licois, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…In rabbits, it has been shown that a diet containing inulin-type fructans affects the caecal microbial activity, morbidity and growth rate in a beneficial way (Morisse et al, 1993;Maertens et al, 2004;Volek et al, 2005Volek et al, , 2007Eiben et al, 2008) or not (Bónai et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the control and MOS diet, the inulin addition strongly influenced the caecal fermentative activity (VFA, pH, ammonia, fermentation pattern) in a beneficial way, which is in agreement with previous studies on rabbits (Morisse et al, 1993;Maertens et al, 2004;Volek et al, 2005) or rats (Juśkiewicz et al, 2004 and. Whatever the diet, the activity of pectinase was higher than the activities of other fibrolytic enzymes (xylanase, inulinase, cellulase), which is in agreement with the hierarchy in fibrolytic activities reported in other studies (Marounek et al, 1995;.…”
Section: Discussionsupporting
confidence: 91%
“…Both the lowest morbidity (P ¼ 0.05) and health risk index (P ¼ 0.03) were recorded in rabbits fed the diet supplemented with inulin. Similarly, a protective effect of fructo-oligosaccharides was recorded in animals experimentally infected with enteropathogenic E. coli (Morisse et al, 1993), and also when inulin was added to a high-pectin diet (Volek et al, 2005). The better health status of rabbits fed the diet with inulin observed in our study was apparently associated with the beneficial effect of inulin on the caecal microbial activity (Table 5).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation